Perkawinan Beda Agama Pasca SEMA Nomor 2 Tahun 2023 dalam Perspektif Hifz al-Din dan Hak Konstitusional Membentuk Keluarga - Mohammad Husni Mubarok; Mumu Fahmudin; Uus Kusmayadi (LEX FAMILIA: Journal of Islamic Family Law, 2026)
The issuance of Supreme Court Circular Letter (SEMA) Number 2 of 2023 marks a paradigm shift in family law in Indonesia, from the practice of judicial activism that opens up loopholes for interfaith marriage, to administrative restrictions that completely close down the practice. This study aims to analyze the legal implications of the SEMA by contrasting two diametric perspectives: the doctrine of religious protection (Hifz al-Din) and the constitutional rights of citizens. This research is a normative legal research with a statutory and conceptual approach. The research findings indicate that: (1) SEMA No. 2 of 2023 is a manifestation of Sadd al-Dzarai (preventive action) of the state to maintain the purity of faith and prevent confusion regarding the status of children's lineage (Hifz an-Nasl); (2) In the Indonesian legal system, the right to form a family (Article 28B of the 1945 Constitution) is categorized as derogable rights whose implementation is limited by religious values ​​as regulated in Article 28J paragraph (2) of the 1945 Constitution; (3) Despite creating legal certainty and unifying judicial interpretation, this SEMA has the potential to trigger legal resistance in the form of legal smuggling through marriages abroad or pseudo-religious conversions. This study concludes that SEMA No. 2 of 2023 confirms Indonesia's position as a state based on the rule of law that places theological validity as an absolute prerequisite for the administrative validity of marriage.